Deformation and Stability of Soft Foundation Improved by Prefabricated Vertical Drains Adjacent to River Bank. (14th November 2018) - Qi, Changqing; Li, Liuyang; Qi, Jiabing
Abstract : This paper presents a finite element analysis on a soft embankment foundation improved by prefabricated vertical drains. A plane strain analysis was performed using equivalent permeability. The predictions of settlement, pore water pressure, and lateral displacement were compared with the available field measurement data, and a general fair agreement was observed. Numerical results indicate that the settlement below the left part of the embankment is obviously larger than that of the right part. The maximum settlement occurs below the left shoulder of the embankment and reaches 1.26 m. The entire shallow foundation shows a movement trend to the left toe. The designed left embankment shoulder was suggested to be 0.16 m higher than the right side. Monitoring and simulation results demonstrate that the foundation is stable during the construction. The factor of safety at the end of the final loading stage is about 1.81. The performance of the embankment is consistent with the design prescriptions, confirming the effectiveness of the soil improved technique included in this project.